2019
DOI: 10.1177/0022057419858346
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resilience and Cyberbullying on Self-Esteem

Abstract: To investigate the effects of resilience and cyberbullying on students’ self-esteem, predictive correlational design was employed as a method of investigation. Data were collected from 580 ninth-grade students at Anatolian High Schools. Findings of the study demonstrated that as the resilience level increases, self-esteem level increases. Also, as cyberbullying increases, self-esteem decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This study found that there is a significant positive correlation between cyber upward social comparison and cyberbullying, which is consistent with Hypothesis 1. The relationship between cyber upward social comparison and cyberbullying has also been reflected in previous studies, which have demonstrated that cyber upward social comparison not only has a negative impact on individual psychological health ( Erdur-Baker and Kavsut, 2007 ; Yang et al, 2010b ; Aboujaoude et al, 2015 ), such as damaging people’s mental health ( Zhou et al, 2013 ), reducing happiness ( Zheng et al, 2020 ), and producing negative emotions of jealousy and depression ( Liang and Wei, 2008 ; Lee et al, 2020 ), but can also lead to irrational cognition and behavior ( Aliyev and Gengec, 2019 ). A study of adolescents found that social comparison was associated with severe bullying behavior ( Stasio et al, 2016 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study found that there is a significant positive correlation between cyber upward social comparison and cyberbullying, which is consistent with Hypothesis 1. The relationship between cyber upward social comparison and cyberbullying has also been reflected in previous studies, which have demonstrated that cyber upward social comparison not only has a negative impact on individual psychological health ( Erdur-Baker and Kavsut, 2007 ; Yang et al, 2010b ; Aboujaoude et al, 2015 ), such as damaging people’s mental health ( Zhou et al, 2013 ), reducing happiness ( Zheng et al, 2020 ), and producing negative emotions of jealousy and depression ( Liang and Wei, 2008 ; Lee et al, 2020 ), but can also lead to irrational cognition and behavior ( Aliyev and Gengec, 2019 ). A study of adolescents found that social comparison was associated with severe bullying behavior ( Stasio et al, 2016 ).…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that compared with face-to-face comparisons, upward comparisons which refer to individuals comparing themselves with those who are better off ( Festinger, 1954 ; Zheng et al, 2020 ) through social media will bring more negative emotions ( Fardouly et al, 2017 ), which may lead to cyberbullying. Many previous studies have explored the factors influencing cyberbullying from the perspective of individuals themselves, such as self-esteem, compassion and prosociality, and found that there is a significant relationship between low self-esteem and cyberbullying ( Aliyev and Gengec, 2019 ; Lei et al, 2020 ; Pascual-Sanchez et al, 2021 ), both empathy and prosociality are effective in reducing cyberbullying ( Ferreira et al, 2021 ; Xu and Wang, 2021 ). Few studies have examined the effects of online social comparison on cyberbullying from an environmental perspective ( Geng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Feeling "different" produces a decrease in self-esteem and a greater number of difficulties in relation to peers [49]. Bullying/cyberbullying also has a negative effect on the self-esteem of victims (e.g., [151]). Self-esteem and cyberbullying maintain strong links according to the role, the context, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Cyber victims often inform a parent or a trusted adult of their abuse [ 81 ]. Furthermore, recent studies have shown a negative association between cyberbullying and self-esteem [ 80 , 82 , 83 , 84 ]. Low self-esteem is one of the outcomes most commonly associated with cyberbullying among children and young people [ 80 ].…”
Section: Overview Of Cyberbullyingmentioning
confidence: 99%